2014
DOI: 10.1159/000363034
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Induces hERG Channel Deficiency through Trafficking Inhibition

Abstract: Aims: The human ether-a-go-go-related gene (hERG) encodes the α subunit of the IKr, which plays an essential role in repolarization of action potentials. hERG channels are targeted by various pro-arrhythmic drugs. Berberine (BBR) was previously found to acutely inhibit hERG currents and prolong action potential duration. The present study aimed to determine long-term effects of BBR on the expression of 135kDa/155kDa hERG and the mechanism. Methods and Results: hERG expression was assessed by western blot. Matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…The previous studies demonstrated BBR and CLR inhibited hERG currents (Volberg et al, 2002;Zhang et al, 2014b). It was confirmed in our study that BBR and CLR could reduce hERG channel currents by accelerating the onset of inactivation.…”
Section: Discussionsupporting
confidence: 90%
“…The previous studies demonstrated BBR and CLR inhibited hERG currents (Volberg et al, 2002;Zhang et al, 2014b). It was confirmed in our study that BBR and CLR could reduce hERG channel currents by accelerating the onset of inactivation.…”
Section: Discussionsupporting
confidence: 90%
“…All major pharmaceutical companies have to monitor the potential risk of LQTS induced by new or existing drugs [12]. The mechanisms underlying this inhibition are mainly two types: one is blocking the channel directly [13]; another is indirectly decreasing the channel expression on the cell surface, such as disruption of channel forward trafficking to the membrane [14] and promotion of the degradation of channel protein [15,16]. As for the trafficking-defective hERG channel, there were reports that a high-affinity hERG blocker would produce pharmacological rescue.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with BBR has been reported to act on numerous targets and signaling pathways underlying pathophysiological process, including proliferation, apoptosis, angiogenesis, migration and invasion in a variety of cancer cells (35)(36)(37). In our previous study, BBR was observed to exert a strong inhibitory effect on hERG potassium channels (22,38,39), which are often aberrantly expressed in carcinoma. Therefore, the present study proposed that BBR may inhibit ovarian cancer by targeting hERG1.…”
Section: Discussionmentioning
confidence: 88%